Gypsum formation from calcite in the atmosphere recorded in aerosol particles transported and trapped in Greenland ice core sample is a signature of secular change of SO2 emission in East Asia. (1st June 2022) - Miyamoto, Chihiro; Iizuka, Yoshinori; Matoba, Sumito; Hattori, Shohei; Takahashi, Yoshio
Abstract: Calcium (Ca) species in aerosol (dust) particles trapped during spring in an ice core at Southeast Greenland (SE-Dome) were examined using X-ray absorption near-edge structure spectroscopy (XANES). The ice core has a record of aerosols from 1957 to 2014, and the samples corresponding to 1971, 1978, 1987, 1995, and 2004 were selected for analysis. Results showed that gypsum fraction to total Ca in the ice core was larger in the recent layers (1995 and 2004) than in the old layers (1971, 1978, and 1987), whereas calcite fraction exhibited the opposite trend. The increased gypsum content was consistent with the increase of SO2 annual emission in China. Given that Ca-bearing dust particles were originally supplied as calcite derived from East Asia, this study suggests that the Ca species in the dust trapped in the ice core can be a good indicator of the secular variation of SO2 emission in this region. Highlights: Calcium species in particles trapped in spring in an ice core in Greenland were analyzed by XANES. Gypsum fraction to total Ca in dust in Greenland Ice Core is a signature of SO2 emission in East Asia. This is a first study on Ca species in particles in the ice core separated by the sublimation of ice.